2013
DOI: 10.3346/jkms.2013.28.8.1187
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence of Klebsiella pneumoniae Extended-Spectrum β-Lactamase in Patients on Renal Replacement Therapy

Abstract: The prevalence of antibiotic resistance is higher in patients undergoing renal replacement therapy (RRT) than in patients who did not undergo RRT. We investigated the presence of KP (Klebsiella pneumoniae) in patients who underwent RRT. All data were collected retrospectively by accessing patient medical records from 2004 to 2011 for the culture results of all patients who were positive for KP. We grouped the patients by the presence of extended-spectrum β-lactamase (ESBL) into a KP ESBL(-) group (KP[-]) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
0
4
1
Order By: Relevance
“…These results demonstrate that infections and the clinical disease status are strongly associated with the severity of illness in CRRT patients during the initial phase of pneumonia (APACHE II and CCI scores) (Planquette et al, 2013;Blot et al, 2014). In contrast to other studies (Lee et al, 2013), BMI was not associated with nosocomial pneumonia in the present study, possibly because this was a retrospective case-control study in a single hospital, increasing the possibility of selection bias.…”
Section: Discussioncontrasting
confidence: 83%
“…These results demonstrate that infections and the clinical disease status are strongly associated with the severity of illness in CRRT patients during the initial phase of pneumonia (APACHE II and CCI scores) (Planquette et al, 2013;Blot et al, 2014). In contrast to other studies (Lee et al, 2013), BMI was not associated with nosocomial pneumonia in the present study, possibly because this was a retrospective case-control study in a single hospital, increasing the possibility of selection bias.…”
Section: Discussioncontrasting
confidence: 83%
“…In contrast, some studies have shown that the DRPs in HDAP are similar to those in nosocomial pneumonia [ 20 , 21 ]. And the risk of multi-drug resistance has been reported to be higher in patients with HDAP than community-acquired pneumonia pathogens such as K. pneumoniae [ 22 ]. Our results proved that P. aeruginosa and MRSA were the most common pathogens in HDAP, supporting the HCAP concept.…”
Section: Discussionmentioning
confidence: 99%
“…4 Of these, Escherichia coli is the most common followed by Klebsiella. 5 Prevalence of E.coli was 28.7% and Klebsiella pneumonia was 16.2% in UTI as monoinfection. 6 Epidemiological studies show an increasing number of patients worldwide suffering from chronic kidney diseases (CKD), which are associated with a risk for progression to end-stage kidney disease (ESKD).…”
Section: Introductionmentioning
confidence: 89%